Mobile Applications for Agriculture and Rural Development - Qiang, Christine Zhenwei; Kuek, Siou Chew; Dymond, Andrew; Esselaar, Steve (World Bank, Washington, DC, 2015)
The dynamic growth of mobile communications technology is creating opportunities for economic growth, social empowerment, and grassroots innovation in developing countries. One of the areas with the greatest potential impact is in the contribution that mobile applications can make to agricultural and rural development (ARD), by providing access to information, markets, and services to millions of rural inhabitants. For both agricultural supply and demand, mobile phones can reduce waste, make delivery more efficient, and forge closer links between farmers and consumers. This report provides policymakers and development practitioners with a guide that facilitates the development and deployment of mobile applications for ARD. It also informs their understanding of the key drivers for promoting such applications and services in their countries. Using James Moore’s (1996) revised definition of ecosystems: economic communities based on interacting organizations and individuals the report identifies a wide range of players in the ecosystem for m-ARD apps, such as mobile network operators, m-app (mobile applications) providers, content providers, and various types of users. M-apps are software designed to take advantage of mobile technology and can be developed for technology besides mobile phones. But mobile phones have many key advantages: affordability, wide ownership, voice communications, and instant and convenient service delivery. As a result, there has been a global explosion in the number of m-apps, facilitated by the rapid evolution of mobile networks and by the increasing functions and falling prices of mobile handsets. M-apps are markedly different in developing countries because they typically run on second-generation (2G) phones rather than smartphones, which are far more common in developed countries. The report reviews country examples and extracts policy lessons and good practices. It also presents detailed studies of cases from Kenya, Philippines, and Sri Lanka, as well as summarizes 92 case studies from Africa, Asia, and Latin America. The goal is to provide a comprehensive understanding of the development impact, ecosystem, and business models for mobile applications in ARD. The report is intended to complement the recent ICT in Agriculture eSourcebook. One of the main findings is that an enabling platform (or platforms) is probably the most important factor for the development of m-ARD apps. Platforms can facilitate interactions among ecosystem players, increase access to users, provide technical standards, and incorporate payment mechanisms.